2021
DOI: 10.1016/j.envpol.2021.117664
|View full text |Cite
|
Sign up to set email alerts
|

Changes in air quality in Mexico City, London and Delhi in response to various stages and levels of lockdowns and easing of restrictions during COVID-19 pandemic

Abstract: The impacts of COVID-19 lockdown restrictions have provided a valuable global experiment into the extent of improvements in air quality possible with reductions in vehicle movements. Mexico City, London and Delhi all share the problem of air quality failing WHO guideline limits, each with unique situations and influencing factors. We determine, discuss and compare the air quality changes across these cities during the COVID-19, to understand how the findings may support future improvements in their air quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…MC not only exhibits among the highest AL incidence rates in the world, but it has also shown variable incidence trends over time, suggesting a potential role of non-genetic factors in disease development ( 44 ), such as an effect of the diversity of environmental exposure across municipalities ( 45 ). Several studies support this possibility, exhibiting differences in exposure among areas or municipalities—for example, to air pollution ( 46 49 ), metalsand chemicals of industrial, agriculture, commercial, and vehicular origin ( 50 , 51 ), and to different near-surface air temperatures. This last variable has become of great epidemiological interest ( 52 56 ) since it is related to the atmospheric distribution of pollutants, and shows great variability between municipalities and areas of MC ( 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…MC not only exhibits among the highest AL incidence rates in the world, but it has also shown variable incidence trends over time, suggesting a potential role of non-genetic factors in disease development ( 44 ), such as an effect of the diversity of environmental exposure across municipalities ( 45 ). Several studies support this possibility, exhibiting differences in exposure among areas or municipalities—for example, to air pollution ( 46 49 ), metalsand chemicals of industrial, agriculture, commercial, and vehicular origin ( 50 , 51 ), and to different near-surface air temperatures. This last variable has become of great epidemiological interest ( 52 56 ) since it is related to the atmospheric distribution of pollutants, and shows great variability between municipalities and areas of MC ( 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have been reported in India ( Lokhandwala and Gautam, 2020 , Naqvi et al, 2021 ), Poland ( Filonchyk et al, 2020 ), Mexico ( Fu et al, 2020 ), Austria ( Lovrić et al, 2021 ), and Florida ( El-Sayed et al, 2021 ). For example, during the strict restrictions period in India, NO 2, PM 2.5 and AOD all decreased by varying degrees compared to the same period in previous years, especially in metropolitan areas such as New Delhi, Mumbai, Bangalore, and Kolkata ( Ranjan et al, 2020 , Singh et al, 2020 , Vega et al, 2021 , Yadav et al, 2020 ). All these above results are consistent with this study, which showed a notable decrease in AOD over the ocean during the lockdown.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, research on the impact of these societal changes on indoor and outdoor air pollution levels across or even within a geographic area may be difficult to interpret due to inconsistent definitions. The differences may contribute to varying results and conclusions of studies examining restriction-related associations with air pollution levels ( Briz- Redón et al, 2022 ; Liu et al, 2021 ; Sarmadi et al, 2021 ; Vega et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%